Research and Practice of Linear Algebra Teaching in the Context of Artificial Intelligence - Yan, Xinhua (Journal of Educational Research and Policies, 2025)
Linear algebra is a fundamental course in science and engineering colleges. The rapid development of artificial intelligence has brought new opportunities and challenges to the teaching of linear algebra. This study integrates artificial intelligence into the teaching of Linear Algebra. We optimize course objectives by leveraging artificial intelligence, reorganize teaching resources with the help of knowledge graphs, carry out diversified teaching processes, and implement multi-dimensional evaluation systems. These measures have effectively enhanced students’ interest in learning and improved teaching effectiveness.